Analisis Kemampuan Siswa dalam Menyelesaikan Soal Geometri pada Asesmen Kompetensi Minimum-Numerasi Sekolah Dasar - Desi Ratna Sari; Epon Nur'aeni Lukman; Muhammad Rijal Wahid Muharram (FONDATIA, 2021)
The implementation of the Minimum Competency Assessment (AKM) which will be held at the school education level, especially at the elementary school level requires preparation in order to carry it out. One of the components that must be prepared is from the students. The readiness of students in this case is seen as very important because as a subject that will be tested in the implementation of the Minimum Competency Assessment (AKM). The basic competencies that are tested on students are divided into two main components, namely reading literacy and numeracy. In the Numerical Minimum Competency Assessment (AKM), one of the materials tested is geometry. This study discusses the analysis of the ability of fourth grade elementary school students in solving geometry problems in the Numeration Minimum Competency Assessment (AKM). This study aims to see and describe the ability of fourth grade elementary school students in solving geometry problems in the Numeration Minimum Competency Assessment (AKM) in terms of the quality of student responses based on the results of students' completeness in completing tests and interviews. This study uses a qualitative description method. Data were obtained from the results of tests and interviews with fourth grade students in the neighborhood of RT 04 Pasirjaya, Tasikmalaya City. There is 1 grade IV student who is the subject of this research. The results of this study indicate that the student's ability to solve geometry problems in the Numeration Minimum Competence Assessment (AKM) is still low, with a percentage of 17.65%.